(3MGTjI cGXe GdYQGbjs - (3GdfLaj, Ydj Hf eMeO QVG cGTa GdZWGA, J (B1350(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3eGA GdeWQ GdLGQj ef GdSeGA HebOGQ jUOb Ydjg GdeWQ YQaG(B...s
(3BNQgG (B:s
(3hde jUd QcYJjf(B... (3Edi BNQg XGgQ GSJMHGH faS GdhVhA hGdEfUGas
(3JHUQI GdYfhGf (B:s
(3JbQjQGJ cGXe GdTjQGRjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U (B504s
(3GdCYdGe(B: (3L(B5(3, U(B19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis